Religiosity and Regional Resilience to Recession. Issue 2 (23rd March 2020) - Cuomo, Raphael E.; Davis, Daniel B.; Goetz, Stephan J.; Shapiro, Josh D.; Walshok, Mary L.
Abstract : Literature shows that religiosity can provide individual resilience to life shocks as well as regional resilience to disasters caused by natural hazards. Related work has examined the complicated links between religion and economic growth. Yet few, if any, studies examine the role of regional levels of religiosity on a region's resilience to recession—or how quickly the employment rate returns to pre‐recession levels (a common measure of resilience in the economics literature). As the recovery period of the Great Recession cools and economists warn of future economic downturns, all known variables that may be linked with regional resilience are worthy of exploration. Using survey results from the Gosling‐Potter Internet Project and General Social Surveys, we applied logarithmic functions to pre‐ and post‐Great Recession employment data for 2, 836 U.S. counties. We found a modest and statistically significant association between religious belief and regional resilience to recession. Religiosity was the strongest of sixteen psychosocial variables that we examined in association with the speed of job recovery; despite having negative links with other economic variables. This has particular salience for more rural economies; policy implications are discussed.